Study on Nonlinear Behavior of Variable Thickness Plates - Hoang That Ton, Lan (International Journal of Engineering and Management Sciences, 2024)
The analysis of variable-thickness plates is much more complicated than that of uniform-thickness plates because variable coefficients occur in the equations. In reality, this analysis is of great interest in various engineering disciplines, such as civil engineering, aerospace engineering, machine design, and so on. Although there is extensive literature on analyses of plates with constant thickness, a rather limited amount of technical literature is available on the solutions to problems dealing with plates with nonuniform thickness. The reason is that the analytical solutions meet insurmountable difficulties. Besides, the nonlinear analysis process also faces more difficulties than the linear analysis of structures. For these reasons, the nonlinear behavior of variable-thickness plates based on a finite element procedure is presented in this study. Although the topic is not special, it will help the engineer have a specific view of the nonlinear bending of the plate with variable thickness. This survey will be based on the change in geometrical parameters. Numerical solutions are then presented to verify the simplicity of this proposed procedure.